ANALISIS PERAN HUKUM SEBAGAI MOTOR PEMBANGUNAN PENDIDIKAN ATAS PUTUSAN MK NO. 3/PUU-XXII/2024 - Muhammad Aris Saifuddin (Fakultas Ilmu Sosial dan Humaniora, 2026)
This study analyzes the role of law as a driving force in educational development through the implementation of Constitutional Court Decision No. 3/PUU-XXII/2024 within the private school financing system. The ruling reaffirms the state’s responsibility to guarantee non-discriminatory basic education, including for students in private schools that perform a social function. The research employs a normative legal method with statutory and conceptual approaches to examine the norms of education financing and the principles of distributive justice. The findings indicate that the Constitutional Court’s decision shifts the financing paradigm from a centralized model toward an inclusive scheme that allows the state to provide proportional subsidies to private schools. The analysis of implementation across regions reveals variations in policy readiness, depending on fiscal capacity, technical regulations, and local governance structures. The study concludes that the effectiveness of the decision requires derivative regulations, strengthened central–local coordination, and reforms in education budget governance. Keywords: education financing, Constitutional Court decision, private schools